Model Studies on Settlement of an Expansive Soil Slope Stabilized with GGBS - Jhansi Kammaluri,; Janaki Ramudu Dudekula,; Sudha Rani Chigurupati, (International Journal of Scientific Research in Science and Technology, 2024)
Expansive soils present significant challenges in civil engineering due to their tendency to undergo volumetric changes with variations in moisture content, often resulting in slope instability and settlement issues. This study investigates the effectiveness of stabilizing expansive soil slopes using Ground Granulated Blast Furnace Slag (GGBS) as an additive. The research employs laboratory-scale model studies to simulate the behaviour of expansive soil slopes subjected to varying levels of GGBS stabilization. The settlement characteristics of the stabilized slopes are analysed under different loading conditions and moisture contents. Experimental results indicate that the incorporation of GGBS enhances the properties of expansive soils, reducing settlement and improving slope stability. The findings contribute to the understanding of sustainable solutions for mitigating settlement issues in expansive soil slopes, offering insights for practical applications in geotechnical engineering.
Keywords: Expansive soil; GGBS; Moisture Content; Settlement and Suction